2015
DOI: 10.1073/pnas.1508838112
|View full text |Cite
|
Sign up to set email alerts
|

N-linked glycosylation of protease-activated receptor-1 at extracellular loop 2 regulates G-protein signaling bias

Abstract: Protease-activated receptor-1 (PAR1) is a G-protein-coupled receptor (GPCR) for the coagulant protease thrombin. Similar to other GPCRs, PAR1 is promiscuous and couples to multiple heterotrimeric G-protein subtypes in the same cell and promotes diverse cellular responses. The molecular mechanism by which activation of a given GPCR with the same ligand permits coupling to multiple G-protein subtypes is unclear. Here, we report that N-linked glycosylation of PAR1 at extracellular loop 2 (ECL2) controls G12/13 ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 43 publications
1
58
0
Order By: Relevance
“…This finding is consistent with other evidence that CPCs do not fully differentiate into functional cardiomyocytes in culture . We also noted that mRNAs for LPAR 1 and LPAR 2 subtypes, and for the thrombin receptor PAR1, all of which can activate RhoA [5153], were highly expressed in mouse CPCs (Fig. S.I.1A).…”
Section: Resultsmentioning
confidence: 94%
“…This finding is consistent with other evidence that CPCs do not fully differentiate into functional cardiomyocytes in culture . We also noted that mRNAs for LPAR 1 and LPAR 2 subtypes, and for the thrombin receptor PAR1, all of which can activate RhoA [5153], were highly expressed in mouse CPCs (Fig. S.I.1A).…”
Section: Resultsmentioning
confidence: 94%
“…It thus remains to be determined if CTR is unique or if there are other class B GPCRs for which their N-glycans modulate ligand binding and/or signaling. Notably, it was recently demonstrated that N-glycans in the class A GPCR PAR1 regulate its G-protein signaling bias 48 . Clearly GPCR N-glycans can modulate their pharmacology and it will be important to determine the structural basis of these effects.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic interactions between ECL and TM residues may act as molecular switches regulating receptor activation, especially in the case of ECL2. While ECL2 displays high variability in sequence, length, and structure even among related receptor subtypes, an impressive number of family A receptors seem to utilize ECL2 in this capacity, including rhodopsin [109112], the serotonin 5-HT4 receptor [113], the V(1a) vasopressin receptor (V1aR) [114], the cannabinoid receptor 1 (CB1) [115117], the β 2 AR [118], the angiotensin II type 1a receptor (ATII1aR) [119, 120], the D2 dopamine receptor (D2R) [121], the C5a complement receptor (C5aR) [122], and protease activated receptor 1 (PAR-1) [123], among others [124, 125]. Considering CXCR4, we recently suggested that manipulation of ECL2 by CXCL12 draws ECL2 toward the orthosteric pocket, thereby moving TMs 2 and 3 closer to one another [13].…”
Section: Beyond Site 15mentioning
confidence: 99%